Engineering Transition Metal Layers for Long Lasting Anionic Redox in Layered Sodium Manganese Oxide. (28th November 2022) - Voronina, Natalia; Yu, Jun Ho; Kim, Hee Jae; Yaqoob, Najma; Guillon, Olivier; Kim, Hyungsub; Jung, Min‐Gi; Jung, Hun‐Gi; Yazawa, Koji; Yashiro, Hitoshi; Kaghazchi, Payam; Myung, Seung‐Taek
Abstract: Oxygen‐redox‐based‐layered cathode materials are of great importance in realizing high‐energy‐density sodium‐ion batteries (SIBs) that can satisfy the demands of next‐generation energy storage technologies. However, Mn‐based‐layered materials (P2‐type Na‐poor Nay [Ax Mn1−x ]O2, where A = alkali ions) still suffer from poor reversibility during oxygen‐redox reactions and low conductivity. In this work, the dual Li and Co replacement is investigated in P2‐type‐layered Na x MnO2 . Experimentally and theoretically, it is demonstrated that the efficacy of the dual Li and Co replacement in Na0.6 [Li0.15 Co0.15 Mn0.7 ]O2 is that it improves the structural and cycling stability despite the reversible Li migration from the transition metal layer during de‐/sodiation. Operando X‐ray diffraction and ex situ neutron diffraction analysis prove that the material maintains a P2‐type structure during the entire range of Na + extraction and insertion with a small volume change of ≈4.3%. In Na0.6 [Li0.15 Co0.15 Mn0.7 ]O2, the reversible electrochemical activity of Co 3+ /Co 4+, Mn 3+ /Mn 4+, and O 2‐ /(O2 ) n‐ redox is identified as a reliable mechanism for the remarkable stable electrochemical performance. From a broader perspective, this study highlights a possible design roadmap for developing cathode materials with optimized cationic and anionic activities and excellent structural stabilities for SIBs. Abstract : The role of Li and Co dual substitution is investigated on the structure and electrochemical properties of P2‐type Nax MnO2 layered cathode material. Li provides possibility for oxygen redox activity due to partial migration from transition metal layer, and Co is crucial for improving conductivity.